Tubuhku Bukan Milikku: Pasal 463 KUHP Baru Ditinjau dari Perspektif Hukum Feminis - Lidwina Nurtjahyo (Jurnal Perempuan, 2023)
This article discusses abortion as perceived in Article 463 of the New Criminal Code as compared to Law No. 36 of 2009 concerning Health. This article is analyzed using the feminist legal perspective. To illustrate the state’s intervention on women’s reproductive health issues in terms of abortion, two cases obtained from the search results of the Supreme Court’s decision directory are included. Article 463 of the New Criminal Code does not provide access for abortion in the context of the health condition of pregnant women as stipulated in the Health Law. Then in the explanatory part of the article, it tends to narrow the concept of sexual violence where abortion is only allowed to be carried out by victims of sexual violence in the form of sexual exploitation/forced prostitution. The findings of this research is that the law does not accommodate women’s experience as a whole, and the fact that pregnancy can occur after a single case of rape. Furthermore, the law does not accommodate the necessity of abortion for pregnant women in emergency health condition. The government and the legislative should produce regulations which accomodate women’s unique experience, especially in terms of reproductive rights issues